WORK GROUP DYNAMICS IN TECHNOLOGY START-UP COMPANIES - Yusuf, Ramayani; Harsono, Deti Mulyo; Hendrayati , Heny; Muhamat, Amirul Afif (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
This research explores work group dynamics in technology startup companies, focusing on factors influencing team performance and innovation. Literature review reveals that tech startups are characterized by flat structures, role flexibility, collaborative culture, and pressure to innovate quickly. Analysis uncovers several key factors in group dynamics. Team composition, including skill and personality diversity, significantly impacts creativity and problem-solving. Clear communication, periodic feedback, and knowledge sharing enhance team learning. Supportive leadership that encourages autonomy and risk-taking is crucial in creating an innovation culture. However, startup teams face challenges such as role ambiguity, interpersonal conflicts, and over-reliance on key individuals. Time pressure and high workloads can cause stress and burnout. Through SWOT analysis, the research suggests proactive strategies to address these challenges. By understanding factors supporting effective teams, startups can position themselves for innovation and sustainable growth. The study highlights the complexity of work group dynamics in technology startups, emphasizing that understanding and managing team interactions is critical for organizational success. It calls for further research to develop strategies for maintaining positive group dynamics in the rapidly evolving startup environment.